Liver cancer cell lines distinctly mimic the metabolic gene expression pattern of the corresponding human tumours - Nwosu, Zeribe C.; Rothley, Melanie; Piorońska, Weronika; Ebert, Matthias; Sleeman, Jonathan P.; Wölfl, Stefan; Meyer, Christoph; Dooley, Steven (Journal of experimental & clinical cancer research, 2018)
Although metabolism is profoundly altered in human liver cancer, the extent to which experimental models, e.g. cell lines, mimic those alterations is unresolved. Here, we aimed to determine the resemblance of hepatocellular carcinoma (HCC) cell lines to human liver tumours, specifically in the expression of deregulated metabolic targets in clinical tissue samples.